ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN PADA WARUNG STEAK & SHAKE DI KOTA BANDUNG : Survey pada Konsumen Warung Steak & Shake di Kota Bandung - Vivi Haryuni, - (2009)
This research leave from existence of issue of request at booth of steak & town shake of Bandung. As for accurate variable in this research is Request, Earnings of consumer, Price, Appetite Consumer, Life Style, and Price Product of Subtitusi. Research method the used is method of Survey Explanatory. And data collecting technique which used in this research is enquette technique, observation and interview. Data-Processing by using doubled linear regresi constructively computer of SPSS 12.0 for Windows. Population in this research is all visitors or all booth consumers of steak&shake town of Bandung. Sampel which used in this research of Technique Sampling of Eksidental that is counted 100 responders. Result test hypothesis showed that, by simultan or by together entire/all variable that is Earnings of consumer, Price, Appetite Consumer, Life Style, and Price Product of Subtitusi have an effect on isn't it or accepted to Request of booth of steak & Town shake of Bandung. But by parsial or partly only Earningses and Price which do not have an effect on or refused to Request of booth of steak&shake town of Bandung. While Appetite consumer, Life Style, and Price Product of Subtitusi have an effect on isn't it or accepted to Request of booth of steak & Town shake of Bandung.